EFEKTIVITAS PELAKSANAAN PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMKN 1 NGASEM KEDIRI TAHUN AJARAN 2023-2024 - Rio Aldo Rivanda; M.E. Winarno (Cahaya Ilmu Bangsa Institute, 2024)
The aim of this research is to determine the effectiveness of Physical Education and Health implementation of learning at SMKN 1 Ngasem Kediri for the 2023-2024 academic year. This research uses descriptive quantitative survey methods. The data instrument used is the Teacher Ability Assessment Tool (APKG) observation sheet. This research focuses on the Physical Education and Health learning process at SMKN 1 Ngasem Kediri. Data collection was carried out in 3 meetings, each meeting had a maximum time of 90 minutes for learning activities. The results of implementation of learning research conducted by 3 PJOK teachers at SMKN 1 Ngasem Kediri used 68 minutes (76%) in the good category with a classification of 61%-80%. These results were obtained by calculating the maximum time of 3 teachers and the average amount of learning time. The data obtained was then analyzed using a quantitative data analysis formula to determine the average total percentage of learning implementation time. Based on the results of systematic research by three Physical Education and Health teachers at SMKN 1 Ngasem Kediri for each learning activity, the time used for preliminary activities was 13 minutes (15%), for core activities 41 minutes (45%), for closing activities 14 minutes (16%). Based on the guidelines for assessing teacher performance during learning implementation, the percentage of preliminary activities is 10%, core activities are 80%, and closing activities are 10%. So it can be concluded that the effectiveness of Physical Education and Health implementation of learning at SMKN 1 Ngasem Kediri for the 2023-2024 academic year has not been effective.